Diagnostic Accuracy of Combined Use of MCV and MCH for the Detection of Thalassaemia Carrier - Haque, Nazmul; Hoque, Sheikh Azimul; Islam, Ariful; Chowdhury, Yamin Shahriar; Debnath, Bithi; Saha, Narayan Chandra (Journal of Current and Advance Medical Research, 2018)
Background: Determination of thalassaemia carrier is the mainstay of prevention and in this context red cell indices like mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) provide valuable tool for determination thalassaemia carrier. Objective: The purpose of the present study was to determine the diagnostic test validity of combined use of MCV and MCH for the determination of thalassaemia carrier. Methodology: This case-control study was carried out in the Department of Pediatrics and Department of Medicine at MAG Osmani Medical College Hospital, Sylhet, Bangladesh from September 2007 to January 2009 for a period of one year and five months. Siblings and cousins of beta thalassaemia major and haemoglobin-E (Hb-E) beta thalassaemia at any age with both sexes were selected for this study. Detailed history and thorough physical examination were performed meticulously. MCV, MCH and Hb-Electrophoresis were performed in all patients. Result: A total 128 siblings and cousins of beta thalassaemia major and Hb- E -beta thalassaemia were recruited for this study. Sensitivity, specificity, positive predictive value and negative predictive value of combine MCV & MCH in determination of thalassaemia carriers are 95.2%, 93.8%, 93.7% and 95.3% respectively. Conclusion: In conclusion combined use of MCV and MCH has high diagnostic validity for the detection of thalassaemia carrier. Journal of Current and Advance Medical Research 2017;4(2):40-43